Zn(II) Based Potential Drug Containing Sertraline as a Strong Antidepressant Agent - Escudero, Graciela (2017)
A novel compound for depression treatment and other psychiatric disorders has been obtained being capable of displaying the combined benefits of sertraline and an essential element such as zinc in order to get better antidepressant and negative side effects. Our working group has synthesized a salt formulation (SerH2 ) 2 +[ZnCl4 ] 2- (C34H36N2 Cl8 Zn, sertralonium tetrachlorozincate(II)). The crystal structure was determined by X-ray diffraction methods. It crystallizes in the monoclinic P21 space group with a=7.3869(2) Å, b=13.2888(4) Å, c=19.3541(6) Å, β=96.596(3)° Å, β=91.792(4)°, and Z=2 molecules per unit cell. Their antidepressant activity in the forced swimming test (FST) proved to be stronger than the one shown by the commercial drug sertraline hydrochloride per se. Furthermore, this compound suppressed the anorexigenic effect caused by the antidepressant and showed an improvement in the assimilation time during in vitro fluorescence studies with bovine serum albumin. The results of this work have led to a patent application which was filed (Nº 20150103320) in Argentine country.